2019
DOI: 10.1371/journal.pone.0199486
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of repetition of self-harm following deliberate self-poisoning in rural Sri Lanka

Abstract: Introduction Repetition of deliberate self-harm is an important predictor of subsequent suicide. Repetition rates in Asian countries appear to be significantly lower than in western high-income countries. Methodological differences in studies, and the impact of access to means of self-harm with comparatively higher lethality have been suggested as reasons for these reported differences. This prospective study determines the rates and demographic patterns of deliberate self-poisoning (DSP), suicide… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 37 publications
3
19
1
Order By: Relevance
“…There is, however, a paucity of evidence from LMICs in south Asia regarding the risk of suicide after a self-harm episode 2 . The few south Asian studies on this issue indicate that the risk of repeat self-harm is lower than in HICs,6, 7, 8, 9, 10 but there have been few prospective studies and most studies to date have been small and of low quality. A large prospective study 10 restricted to people who had self-poisoned in a rural region of Sri Lanka reported that the risk of repeat self-poisoning at 12 months was 5·7% (95% CI 5·0–6·4) and of suicide (all methods) at 2 years was 0·7% (0·4–0·9), considerably lower than the risks reported in HICs.…”
Section: Introductionmentioning
confidence: 99%
“…There is, however, a paucity of evidence from LMICs in south Asia regarding the risk of suicide after a self-harm episode 2 . The few south Asian studies on this issue indicate that the risk of repeat self-harm is lower than in HICs,6, 7, 8, 9, 10 but there have been few prospective studies and most studies to date have been small and of low quality. A large prospective study 10 restricted to people who had self-poisoned in a rural region of Sri Lanka reported that the risk of repeat self-poisoning at 12 months was 5·7% (95% CI 5·0–6·4) and of suicide (all methods) at 2 years was 0·7% (0·4–0·9), considerably lower than the risks reported in HICs.…”
Section: Introductionmentioning
confidence: 99%
“…THK is the main referral center for the 1.6 million population of the district, [12] and receives more than 53% of the total deliberate self-poisoning cases of the district. [6] Procedure Sample and sampling:…”
Section: Study Design and Study Settingmentioning
confidence: 99%
“…This nding may also partially explain the lower repetition rates of self-harm, observed in Sri Lanka. [6,27] In this Sri Lankan context a greater focus on non-psychiatric and medical interventions many be appropriate. In rural Sri Lanka, self poisoning seems to be the preferred method of dealing with di cult situations [28].…”
Section: Rates Of Psychiatric Morbiditymentioning
confidence: 99%
See 1 more Smart Citation
“…In a review article, Carrol et al reported that fewer Asian patients attempted suicide by pesticide at risk of repetition comparing to European patients, 10 nevertheless, a 2019 prospective cohort study in Sri Lanka showed 48.7% of suicide repeaters by pesticide chose pesticide again in repeated attempts. 11 In a study of 39 Fiji patients who attempted suicide mostly by drug and pesticide ingestion, Aghanwa 12 reported that social problems and psychiatric comorbidities were noted in 64.1% of cases. Our previous study 13 of 157 Taiwanese patients who attempted suicide by paraquat ingestion revealed that mood disorders (54.0%) were the most common psychiatric comorbidities.…”
Section: Introductionmentioning
confidence: 99%